2022
DOI: 10.1093/jnen/nlac026
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Cerium Oxide Nanoparticles to Treat Spinal Cord Injury in Rats

Abstract: This study investigated the effects of local injection of cerium oxide nanoparticles (CeONPs) in a rat spinal cord injury (SCI) model. Thirty-six adult male Wistar rats were divided into 4 groups: controls (healthy animals), sham (laminectomy), SCI (laminectomy+SCI induction), and treatment (laminectomy+SCI induction+intrathecal injection of CeONPs immediately after injury). SCI was induced using an aneurysm clip at the T12-T13 vertebral region. Motor performance and pain threshold tests were performed weekly;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In the motor function of the left paw, it was observed that the Scaffold alone could not improve movement, but the Scaffold-CeO 2 significantly improved the left paw movement compared to the SCI and Scaffold groups, although this improvement did not reach the level of the control group. This result is consistent with the results of other studies that showed injection of cerium oxide nanoparticles has helped to improve motor function after spinal cord injury [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the motor function of the left paw, it was observed that the Scaffold alone could not improve movement, but the Scaffold-CeO 2 significantly improved the left paw movement compared to the SCI and Scaffold groups, although this improvement did not reach the level of the control group. This result is consistent with the results of other studies that showed injection of cerium oxide nanoparticles has helped to improve motor function after spinal cord injury [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Kim et al also showed that CeONPs had an antioxidant effect in spinal cord injury and subsequently improved the functional recovery in rats after mild traumatic brain injury [ 53 ]. In last work our team also demonstrated the healing effect of soluble CeONPs on neuronal regeneration after SCI [ 54 ] but at the present study, the release of nanoparticles was continuously from the fabricated scaffold, and the novelty of this study lies in this issue. In the present study, we investigated the effect of a gelatinous poly(ε-caprolactone) scaffold containing CeONPs (Scaffold-CeO 2) implanted at the site of injury on nerve cell growth and pain relief in a SCI animal model.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the following week, we found the rats’ motor function significantly improved which was consistent with previous studies. 28 In addition, the mechanical PWT and thermal PWL were increased, suggesting that CONPs possess a pain-relive effect. Some recent studies have implicated the analgesia effect of CONPs in various animal models.…”
Section: Discussionmentioning
confidence: 98%
“…Some recent studies reported that nanoceria could repair the injured spinal cord and promote SCI rats’ locomotor function recovery. 16 , 28 Here, we synthesized CONPs nanoparticles using the hydrothermal method. Besides, we adjusted the base concentration and reaction temperature in hope of getting a smaller nanoceria than that described by Jong-Wan Kim et.al 17 There are mainly two reasons for doing so: first, the smaller particle size of nanoceria ensures a higher concentration of oxygen vacancy on the surface and more active biological activity; 29 second, smaller nanoceria displayed better metabolism and biosafety.…”
Section: Discussionmentioning
confidence: 99%